2021
DOI: 10.3390/foods10081817
|View full text |Cite
|
Sign up to set email alerts
|

Physicochemical, Mineral and Sensory Characteristics of Instant Citrullus lanatus mucosospermus (Egusi) Soup

Abstract: Defatted egusi flour offers a food option high in protein and essential micronutrients. An instant processing method was adopted in a ready-to-eat instant soup using egusi grit, hydrocolloid, and defatted flour. A D-optimal quadratic mixture model was used to study the effect of the independent variables (grit, flour, and hydrocolloid) qualities. The quadratic model was adequate to navigate the design space for taste and appearance. The numerical optimization for appearance and taste of instant soup (IES) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…citroides, locally called citron melon or makataan [2]. Makataan melons are under cultivation in South Africa [7]. Makataan seed can be dehulled, roasted, or eaten as it is, or its seeds can be cold-pressed to obtain a nutritious oil (68% w/w dry weight) high in omega-6 fatty acids [2].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…citroides, locally called citron melon or makataan [2]. Makataan melons are under cultivation in South Africa [7]. Makataan seed can be dehulled, roasted, or eaten as it is, or its seeds can be cold-pressed to obtain a nutritious oil (68% w/w dry weight) high in omega-6 fatty acids [2].…”
Section: Introductionmentioning
confidence: 99%
“…The potential of makataan melon seeds is yet to be explored. This seed's sole industrial application, called 'Kalahari seed', involves cold-pressing to extract oil [7,8]. Limited information exists regarding its nutritional and functional attributes and the potential hydrocolloid properties of its flour.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It should be noted that none of these studies have mentioned the adverse toxicological effects of date kernel powder; however, El Sheikh et al (2014) have confirmed in vitro cytotoxic activity of roasted date kernels. Also, considering the available literature, no research on the evaluation of the effect of this valuable and cheap functional sub‐product on the quality of dry soup has still been undertaken (Abdel‐Haleem & Omran, 2014; Niththiya et al, 2014; Olubi et al, 2021; Upadhyay et al, 2017). On the other hand, based on the studies, the highest content of antioxidant compounds in dates is included in their kernels, which encompass phenolic compounds (Wahini, 2016).…”
Section: Introductionmentioning
confidence: 99%